Comparison of Ammonia Removal from Ground Water in Attached Growth Process Using Over-burnt Brick with Suspended Growth Process without Any Media - Dhungana, Kirti; Amatya, Iswar Man; Maharjan, Rabin; Devkota, Subigya; Katwal, Kamal (International Journal on Engineering Technology, 2024)
Rising amount of ammonia in groundwater is rising problem in groundwater of Kathmandu. This has led to various diseases like blue baby syndrome to arise. So, it is necessary for efficient and safe removal of ammonia from drinking water. Since the physical-chemical system includes the major disadvantages of high operation and maintenance cost, the biological nitrification system can only be a good alternative to remove ammonia from ground water. Hence, an attempt is done in this research to treat ammonia contaminated water by biological nitrification process. Three reactors were constructed in series with media of over-burnt brick and other three in series were constructed without media. The study was carried out for five different flow rates of 10, 14.4, 18.8, 27.6 and 38.8 ml/min. Based on laboratory test the efficiency of these five different flow rates was plotted and conclusions were reached. Achievement of continuously increasing efficiency, which reached to 95–100% in the reactor provided with over-burnt media; reflects a success in the assumption that the over-burnt brick is good media to be used in bio filters for nitrification. The reactors with media have more efficiency than reactors without media. An average efficiency of 56.48% for reactors with media and 37.55% for reactors without media was observed for all the flows. The difference of 18.72± 0.2 was found between reactor with media and reactor without media in both series and single reactor. Low flow rates showed better ammonia removal than flow rates with higher flow rates such that a hydraulic retention time of 7.29 hour per reactor can be taken as design criteria for nitrification using over-burnt brick as media.